Data cooperative - Alexander Fink (Internet Policy Review, 2024)
Data cooperatives are a type of data intermediary using long established cooperative models and global regulatory affordances to manage data with or on behalf of members (data producers) for the benefit of members or for trade with external queriers (data users).
Keywords: 300; Data; Data cooperative; Data intermediaries